Improving teaching and learning activities in subjects from “Human and society” curricular area at secondary school level. Case study for a school in Romania - Simion, Cristina; Enache, Rodica Gabriela (Technium Social Sciences Journal, 2022)
The present article is an analysis of some efficient didactic strategies for the teaching-learning activities in subjects from “Human and Society” curriculum area at Secondary school and a presentation of a quasi-experimental psychological-pedagogical research that had the objective to measure the effects over students’ performances in subjects from “Human and Society” curricular area following the participation of teaching staff training programs and international mobility.